2000
DOI: 10.1152/jappl.2000.88.4.1397
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses during anemia and its correction in lambs

Abstract: There is limited information available on which to base decisions regarding red blood cell (RBC) transfusion treatment in anemic newborn infants. Using a conscious newborn lamb model of progressive anemia, we sought to identify accessible metabolic and cardiovascular measures of hypoxia that might provide guidance in the management of anemic infants. We hypothesized that severe phlebotomy-induced isovolemic anemia and its reversal after RBC transfusion result in a defined pattern of adaptive responses. Anemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 47 publications
4
21
0
1
Order By: Relevance
“…Nelle et al [14] reported no change in non-invasively measured blood pressure. A decrease in HR after red cell transfusion has been more consistently reported in anaemic subjects [8,9,13,14,26], most probably explained by mitigation of tissue hypoxia and concomitant tachycardia [27]. We observed a similar, albeit statistically non-significant ( P =0.062), trend towards decreased HR after the transfusion during the early neonatal period, although the infants in the present study were not anaemic.…”
Section: Discussionsupporting
confidence: 74%
“…Nelle et al [14] reported no change in non-invasively measured blood pressure. A decrease in HR after red cell transfusion has been more consistently reported in anaemic subjects [8,9,13,14,26], most probably explained by mitigation of tissue hypoxia and concomitant tachycardia [27]. We observed a similar, albeit statistically non-significant ( P =0.062), trend towards decreased HR after the transfusion during the early neonatal period, although the infants in the present study were not anaemic.…”
Section: Discussionsupporting
confidence: 74%
“…[17] This was relevant clinically in our study when we observed a statistically significant decrease in the heart rate of our infants after transfusion, suggesting that this decrease in heart rate was most probably explained by the migitation of tissue hypoxia and concomitant tachycardia. [18]…”
Section: Discussionmentioning
confidence: 99%
“…First, this capability adds to the potential utility of the sheep as a model for preclinical testing 26. Second, we speculate that extending the studies of RBCs labeled with multiple distinct biotin densities to humans including sequential measurement of RCV and red cell survival (e.g., 24-hour survival post-transfusion recovery and circulating lifespan) will be successful and will offer the opportunity to perform these studies in human fetuses, infants, children, and pregnant women.…”
Section: Discussionmentioning
confidence: 99%